The motion of colored charged particles in the SU (3) non-Abelian model of dark matter - Dzhunushaliev, V.D.; Проценко, Н.А. (Recent Contributions to Physics, 2017)
A method of experimental verification of non – Abelian dark matter model where the dark matter is a classic non-Abelian SU (3) gauge field Yang – Mills is proposed. The method is based on the analysis of motion of charged particles in the color non – Abelian gauge field. For the analysis of the motion we use Wong equations that are the generalization of the second Newton law for particles with a color charge. In order to find numerical solution of Wong equations we write them in dimensionless form. Using monopole ansatz of SU(3) Yang - Mills gauge theory we obtain the expressions for gauge potentials and field strengths. Using Yang – Mills equations we obtain asymptotic expressions of these fields. Wong equations are numerically solved with the help of these expressions. The result of calculations is presented as the mechanical trajectories of color charged particles.
Keywords: Wong equations, Yang – Mills equations, colored particles, non – Abelian gauge field